Employees' Managed Resentment: Public Procurement and the Part of Emotions in Social Change. (February 2020) - Benjamin, Orly
Resentment, that is triggered by deprived entitlement, was suggested as particularly salient for energizing action and change in labor relations. However, its relationship with estrangement has not yet been examined as relevant to social change in times of contracting out services. I investigate this question in my research of public procurement as a mode of contract-based service delivery, examining two types of related jobs. The analysis of interviews with 30 employees and 12 administrators, all women, revealed the emergence of managed resentment and the conditions of its coexistence with estrangement. I demonstrate a learning process in which resentment energizes action but encounters lack of recognition. Managed resentment follows but remains protected from estrangement only by positive emotions created in care relations. I discuss possible meanings of these subjective developments for social change in the contexts of women's encounter with lack of recognition of their skilled or professional contributions.